2011
DOI: 10.1175/2011bams3215.1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Total Column Water Vapor by Pointing an Infrared Thermometer at the Sky

Abstract: W ater vapor is the constituent of the atmosphere that is most responsible for weather, the hydrological cycle, and the maintenance of Earth's temperature within a range that supports life as we know it (Mockler 1995). Furthermore, water vapor condensed on sulfate and other hygroscopic aerosols can significantly increase the aerosol optical thickness of the atmosphere (Tang 1996).The direct and indirect influence of water vapor on weather, climate, and the environment is so important that there is significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
(15 reference statements)
2
15
0
Order By: Relevance
“…The PW, however, was higher in the Tmin events than in the Tmax events, suggesting that the Tmin events are more related to downward longwave fluxes, as mediated by moisture (and temperatures) aloft. This hypothesis is supported by the relationship between PW and infrared sky temperature measured by an IR thermometer (Mims et al 2011). While this relationship was not statistically significant in the composites that included all of the days in the event, the evolution composites indicated statistically significant differences in PW between the Tmax and Tmin events, and the composites that removed the overlapping events showed a greater distinction in moisture between the two types.…”
Section: Discussionmentioning
confidence: 86%
“…The PW, however, was higher in the Tmin events than in the Tmax events, suggesting that the Tmin events are more related to downward longwave fluxes, as mediated by moisture (and temperatures) aloft. This hypothesis is supported by the relationship between PW and infrared sky temperature measured by an IR thermometer (Mims et al 2011). While this relationship was not statistically significant in the composites that included all of the days in the event, the evolution composites indicated statistically significant differences in PW between the Tmax and Tmin events, and the composites that removed the overlapping events showed a greater distinction in moisture between the two types.…”
Section: Discussionmentioning
confidence: 86%
“…It presents an exponential function relationship, which was consistent with previous studies. 19 The T sky in the atmospheric window (i.e., SRF 2) mainly ranges from 165 to 290 K, whereas that covering 6.3 μm water vapor absorption bands (i.e., SRF 1) ranges from 210 to 290 K. This indicated that a larger dynamic range (i.e., 165 to 290 K) is required for T sky measurements if the thermometers or infrared radiometers operate in atmospheric window bands. In contrast, it is required to cover 170 to 280 K if the radiometer works in a wider spectral range, which includes water vapor and ozone absorption bands.…”
Section: Pwv Retrieval Algorithm By Neural Network Modelmentioning
confidence: 99%
“…18 Mims proposed a simple method for PWV estimation from the zenith clear sky brightness temperature (T sky ) by a handheld infrared thermometer. 19 Their results showed that the T sky is related to the GPS PWV. The exponential function was used to convert T sky to PWV, the RMSE of PWV estimation is ∼4.0 mm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although TPW can be obtained from infrared measurements on satellite platforms such as GOES-R (Schmit et al, 2018(Schmit et al, , 2017, potentially large observation angles can result in degraded spatial resolution, and may not provide adequate information for numerical weather prediction models to take into account local variations in TPW. Building upon a method using low-cost materials to determine TPW based on infrared temperature measurements of the zenith sky (Mims et al, 2011), we examined whether similar tech-1 https://doi.org/10.5194/amt-2021-130 Preprint. Discussion started: 20 May 2021 c Author(s) 2021.…”
Section: Introductionmentioning
confidence: 99%